IBN TAYMIYYA’S VISION ON PUBLIC INTEREST AND PROSPERITY WITHIN ISLAMIC LAW - Jalili, Ismail; Syaifuddin, Helmi; Ulfa, Fadillah; Sa'diah, Halimatus; Solihu, Abdul Kabir Hussain (Ulul Albab: Jurnal Studi Islam, 2024)
This article examines Ibn Taymiyya's vision of governance, spotlighting the concepts of public interest (mas{lahah) and prosperity (falâh) within the Islamic law (sharî’a) framework. The increasing importance of Islamic governance in contemporary political discussions, particularly in Muslim-majority societies striving to harmonize tradition with modernity, underscores the relevance of this inquiry. The primary aim is to synthesize existing scholarship on Ibn Taymiyya's contributions to statecraft and its ethical dimensions, elucidating how his principles can guide contemporary governance. The literature reveals a diverse yet fragmented landscape, encompassing historical analysis, theological discourse, and socio-political critiques, reflecting a burgeoning interest in the intersection of Islamic jurisprudence and governance models. This study employs qualitative analysis of both primary texts and contemporary interpretations, creating a nuanced overview of Ibn Taymiyya's political thought. The results indicate that he champions a governance model that prioritizes community welfare, grounded in ethical accountability and justice. His vision emphasizes the alignment of state policies with principles of justice and public interest, asserting that adherence to Islamic values is essential for achieving prosperity. In conclusion, this study contends that Ibn Taymiyya’s insights are relevant and crucial for modern statecraft, providing a robust framework for embedding ethical considerations into governance.